Unveiling the role of epigenetic mechanisms and redox signaling in alleviating multiple abiotic stress in plants - Shriti, Surbhi; Bhar, Anirban; Roy, Amit (Frontiers in Plant Science, 2024)
Anthropogenic activities and subsequent global climate change instigate drastic crop productivity and yield changes. These changes comprise a rise in the number and severity of plant stress factors, which can arise simultaneously or sequentially. When abiotic stress factors are combined, their impact on plants is more substantial than that of a singleton stress factor.One such impact is the alteration of redox cellular homeostasis, which, in turn, can regulate downstream stress-responsive gene expression and resistance response. The epigenetic regulation of gene expression in response to varied stress factors is an interesting phenomenon, which, conversely, can be stable and heritable. The epigenetic control in plants in response to abiotic stress combinations and their interactions with cellular redox alteration is an emerging field to commemorate crop yield management under climate change. The article highlights the integration of the redox signalling pathways and epigenetic regulations as pivotal components in the complex network of plant responses against multi-combinatorial stresses across time and space. This review aims to lay the foundation for developing novel approaches to mitigate the impact of environmental stresses on crop productivity, bridging the gap between theoretical understanding and practical solutions in the face of a changing climate and anthropogenic disturbances.